P27Kip1 inhibits systemic autoimmunity through the control of Treg cell activity and differentiation. Issue 2 (28th January 2013) - Iglesias, Marcos; Postigo, Jorge; Santiuste, Inés; González, Jovanna; Buelta, Luis; Tamayo, Esther; Merino, Jesús; Merino, Ramón
Abstract Objective Despite the importance of Treg cells in the maintenance of immunologic tolerance, the mechanisms that control their generation and activity are unknown. Since the cell cycle inhibitor p27Kip1 (p27) was involved in T cell anergy, we undertook this study to explore its role in both Treg cell processes. Methods The development of type II collagen–induced arthritis (CIA) and lupus‐like abnormalities was compared between transgenic mice overexpressing human Bcl‐2 in T cells (BCL2‐TgT mice) and nontransgenic mice that were deficient or not deficient in p27. The contribution of Treg cells to disease evolution was also explored. Finally, the in vitro activity of Treg cells and their differentiation from naive CD4+ cells was compared between these strains of mice. Results BCL2‐TgT mice were protected against CIA by a Treg cell–dependent mechanism. In association with this protection, the overexpression of Bcl‐2 in T cells enhanced the differentiation and activity of Treg cells. Both Bcl‐2 effects were independent of its antiapoptotic activity but dependent on its capacity to induce the expression of p27 that augmented the strength of transforming growth factor β (TGFβ) signaling in T cells. Accordingly, down‐modulation of p27 expression in BCL2‐TgT mice promoted CIA. In addition, p27 deficiency in aged C57BL/6 mice reduced the number and activity of Treg cells and induced the development of mild lupus‐like abnormalities. Conclusion Our results point to p27 as a critical regulator of Treg cell differentiation and function through the positive modulation of TGFβ signaling strength in T cells.